Tombs : Junji Ito story collection - Itō, Junji, 1963-; Allen, Jocelyne, 1974- (VIZ Media, LLC, 2023)
"Countless tombstones stand in rows throughout a small community, forming a bizarre tableau. What fate awaits a brother and sister after a traffic accident in this town of the dead? In another tale, a girl falls silent, her tongue transformed into a slug. Can a friend save her? Then, when a young man moves to a new town, he finds the house next door has only a single window. What does his grotesque neighbor want, calling out to him every evening from that lone window?"--Provided by publisher.